Analysis of the dynamics of the temperature regime of the North-Western Black Sea region in the context of global climate changes - Prokofiev, Oleg; Goncharova, Liudmyla (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Formulation of the problem. This study aligns with UN Sustainable Development Goal No. 13 – Climate Action – by addressing key climate-related challenges impacting sustainable development in Ukraine. It focuses on analyzing the dynamics of temperature-dependent natural resource indicators in the North-western Black Sea region, a vital industrial-agricultural area. Understanding the thermal regime is essential for adapting socio-economic sectors to climate change. The research supports planning and resilience in southern Ukraine under changing climate conditions. It is part of projects at the Faculty of Hydrometeorology and Ecology, Odesa I.I. Mechnikov National University, including: ’Forecasting hazardous meteorological phenomena over the southern regions of Ukraine’ (No. DR 00115U006532); ’Comprehensive probabilistic-forecasting modeling of extreme hydrological events on the rivers of southern Ukraine to ensure sustainable water use under climate change conditions’ (No. DR 0121U010964); ’Zoning of Ukraine’s territory based on vulnerability to climate change and selection of optimal adaptation pathways.’ This work fills critical gaps in the study of regional climate dynamics. Analysis of previous research it proves the importance of studying the climatic indicators of the temperature regime of the North-Western Black Sea region, which is a leading highly developed industrial-agricultural region of Ukraine. The underestimation of certain aspects of the dynamics of climatic characteristics of the regional climate in the context of global climate change has led to these aspects being still insufficiently studied today. The purpose. This article aims (using the Odessa station as an example) to present the results of a physical-statistical approach to determining regional responses in the main indicators of the temperature regime of the North-Western Black Sea region to the changes occurring in the climate system of the present period. Research methods. The implementation of the physical-statistical approach was conducted using classical methods of statistical and graphical analysis. Presentation of the main research material. Based on long-term empirical data, it was determined that during the period from 2013 to 2023, compared to the standard climatic period (1961-1990), the average number of days with maximum air temperature above 0°C increased in all winter months. For the studied area, January remains the coldest winter month, with an average of 23,5 days with a minimum air temperature of 0°C or lower. The beginning of the 21st century is characterized by warmer winter conditions (compared to the period 1961-1990), which has led to a decrease in the number of days with low air temperature. Over the last eleven years (2013-2023), 65 thaw periods were registered. They most frequently occurred in January, in December and in February. Research results and Practical value. The obtained results provide a basis for analyzing the dynamics of regional climate changes in the context of global climate change. The rational and timely application of the climate information presented in this article will contribute to the development of effective adaptation pathways, which, in turn, will make a significant contribution to ensuring the sustainable development of Ukraine. Future tasks will focus on researching the thermal regime indicators of other stations in the North-Western Black Sea region, involving additional empirical data.